2022
DOI: 10.1088/1758-5090/ac925a
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of 3D breast cancer models for dissecting the cytotoxic response of human T cells expressing engineered MAIT cell receptors

Abstract: Immunotherapy has revolutionized cancer treatment with the advent of advanced cell engineering techniques aimed at targeted therapy with reduced systemic toxicity. However, understanding the underlying immune–cancer interactions require development of advanced three-dimensional (3D) models of human tissues. In this study, we fabricated 3D tumor models with increasing complexity to study the cytotoxic responses of CD8+ T cells, genetically engineered to express mucosal-associated invariant T (MAIT) cell recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In most of these studies, mainly the less aggressive MCF7 (luminal A) or the more aggressive triple-negative (MDA-MB-231) breast cancer cell lines were used. Only a few papers describe multi-cellular models, 3D models combined with vessels, adipocytes, fibroblasts or 3D bioprinted tissue mimetic in vitro structures in the field of breast cancer research ( 82 , 83 , 109 ). We also have experience printing triple-negative breast cancers using MDA-MB-23 and MDA-MD-468 cell lines.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these studies, mainly the less aggressive MCF7 (luminal A) or the more aggressive triple-negative (MDA-MB-231) breast cancer cell lines were used. Only a few papers describe multi-cellular models, 3D models combined with vessels, adipocytes, fibroblasts or 3D bioprinted tissue mimetic in vitro structures in the field of breast cancer research ( 82 , 83 , 109 ). We also have experience printing triple-negative breast cancers using MDA-MB-23 and MDA-MD-468 cell lines.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Alginate-based bioinks stabilised and CaCl 2 stabilised preferably avoiding mutagenic UV for human cell printing (e.g., in the case of GELMA) ( 155 ). In the other part of these works, matrigels decellularized ECM with additional collagen or other gradients, GELMA, fibrinogen or hyaluronic acid (HA), and PEG- (polyethylene glycol) based materials are also used ( 82 , 109 , 124 ). The main problem with the published descriptions and protocols is that the used biomaterials are different and not fully characterised or specified in most of the papers.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To create a tumor-immune interaction model, Dey et al. printed a ring of T cells into a collagen bath and deposited a single MDA-MB-231/human dermal fibroblast spheroid in the center ( Figure 2D ) ( 73 ). In each of the print designs, cancer cells migrated from the central spheroid and invaded into the collagen matrix.…”
Section: D Bioprintingmentioning
confidence: 99%
“…In one study, Dey et al. developed 3D tumor-T cell platforms that allowed for the study of complex immune-cancer interactions and the evaluation of genetically engineered CD8 + T cells expressing mucosal-associated invariant T (MAIT) cell receptors against breast cancer cells ( 73 ). Their study showed that the engineered T cells effectively eliminated tumors in 3D culture.…”
Section: Challenges and Opportunities Of Using 3d Models To Study The...mentioning
confidence: 99%
“…By providing such precise control, hydrogels enable the creation of in vitro models that more accurately recreate the histopathology of the infiltrated immune cells in the tumor, thus significantly improving the usefulness of these models in cancer research. Moreover, the use of bioprinting to exert spatial control over engineered cell-laden hydrogels has been demonstrated by several research groups to create 3D constructs, which can further enhance the realism and intricacy of in vitro cancer-TIL models. …”
Section: Introductionmentioning
confidence: 99%